Enhancing Students’ Mathematics Learning Outcomes through Problem-Based Learning - Pardede, Agnes Pesta Kristiani; Tuerah, Philotheus E.A.; Ermita, Ermita; Shidiq, Galih Albarra (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2025)
Low levels of student engagement and learning motivation have led to limited critical thinking skills, which in turn have affected students’ learning outcomes that remain below the Minimum Mastery Criteria (MMC). This study aims to determine whether students who received instruction through the Problem-Based Learning (PBL) model achieved higher mathematics learning outcomes than those taught using the conventional (lecture-based) model on the topic of Relations and Functions. This research employed a quasi-experimental method with a pretest–posttest control group design. Population consisted of eighth-grade students from SMP Negeri 3 Tondano, while the samples were class VIII-A (22 students) as the experimental group and class VIII-B (17 students) as the control group. The research instrument comprised written essay tests administered as pretests and posttests in both groups. Data were analyzed using inferential statistical procedures. Data were first tested for normality using the Liliefors test, followed by a homogeneity test (F-test). After both assumptions were met, an independent samples t-test (two-tailed) was performed to test the hypothesis. The results showed a statistically significant difference in mathematics learning outcomes between students who learned through the PBL model and those taught using the conventional lecture-based method. Therefore, it can be concluded that the implementation of the PBL model effectively enhances students’ mathematics learning outcomes on the topic of Relations and Functions, providing evidence that active, problem-oriented instruction can improve students’ conceptual understanding and achievement in mathematics.